The Role of Metacognitive Instruction in Developing ESL/EFL Listening Abilities: A Theoretical and Empirical Review - Ani Fiani (Linguistic, English Education and Art (LEEA) Journal, 2018)
Due to metacognition, as a psychological concept, has been a focus of educational researchers and become a potential to empower students to improve their own learning; increase the meaningfulness of learning, especially among students who are having problems in learning; and become successful learners, the present paper implicatively investigates the possible role of metacognitive instruction in developing ESL/EFL listening abilities among students by providing theoretical and empirical foundations drawn from the literature. To elicit the purpose of this article, the literature study was used. This study reviewed several recent research papers in the last 10 years related to the implementation of metacognitive instruction in order to elicit the information of the possibilities in developing ESL/EFL students’ listening comprehension abilities. Based on a detailed analysis and review of the research articles, there were some themes related to the possibility role of implementing the instruction not only developing ESL/EFL listening abilities, but also metacognitive knowledge and metacognitive awareness. Moreover, the instruction enables ESL/EFL students to increase their awareness of the listening process by improving richer metacognitive knowledge about themselves as listeners, the nature and demands of listening tasks, and listening strategies. This instruction they may encourage them to have an ability to regulate their own learning in and outside ESL/EFL classrooms. Therefore, based on the literature review and analysis above, ESL/EFL teachers will regard the important role of metacognition and attempt to implement the instruction as an alternative of effective teaching ways to develop ESL/EFL students’ listening abilities in and outside the classroom independently, particularly in the context of higher education in Indonesia. Keywords: metacognition, metacognitive awareness, metacognitive instruction, listening abilities